The Influence of Autogenic Relaxation in Lowering Stress and Blood Sugar Levels in Clients with Type II Diabetes Mellitus - Farida, Ida; Meirina; Ekasari, Mia Fatma (Babali Nursing Research, 2024)
Introduction: Stress is identified as one of the modifiable risk factors for diabetes mellitus. High stress levels can trigger an increase in blood sugar levels. There are four approaches to controlling blood sugar levels: pharmacological therapy, nutritional therapy, physical activity, and education on self-management of diabetes, such as implementing autogenic relaxation therapy. Autogenic relaxation is a form of mind-body intervention that originates from within an individual, involving short phrases or sentences that promote a sense of tranquility. The aim of this research is to examine the influence of autogenic relaxation in reducing stress levels in clients with Type II diabetes mellitus. Methods: The research design employed is a quasi-experiment with a group control and pre-post-test. The intervention group received autogenic relaxation sessions lasting 15-20 minutes, six times with a one-day interval between sessions. The control group was observed without any intervention. Results: The results revealed a significant difference between the intervention and control groups for the variables of stress (p-value 0.000) and blood sugar (p-value 0.008). Conclusion: The analysis indicates that autogenic relaxation therapy can effectively reduce stress and blood sugar levels in Type II diabetes mellitus clients. We recommend that healthcare services implement autogenic relaxation therapy programs to assist clients with Type II diabetes mellitus in addressing stress-related issues and managing their blood sugar levels